AIDS-related knowledge, stigma and customary beliefs of South African construction workers. Issue 6 (3rd June 2017) - Govender, Rajen; Bowen, Paul; Edwards, Peter; Cattell, Keith
ABSTRACT: Customary beliefs about the cause/s of AIDS are significantly related to whether or not individuals will undergo HIV testing. This study examined the cultural beliefs of construction workers in terms of their demographic and lifestyle behavioural characteristics, and their AIDS-related knowledge and stigma attitudes, to help inform improved work-based AIDS-education interventions by construction firms. A total of 512 workers drawn from 6 firms operating on 18 construction sites in the Western Cape province participated in the study. Thirty-seven per cent of participants either endorsed customary beliefs/explanations about the cause of AIDS, or were unsure. AIDS-related knowledge proved a significant differentiator of participants endorsing customary beliefs (aOR = 0.8, 95% CI, 0.6–1.0), or being unsure (aOR = 0.5, 95% CI, 0.4–0.6), compared to participants not endorsing such beliefs. Stigma (aOR = 1.3, 95% CI, 1.1–1.7) proved a significant differentiator of participants with more polarized beliefs, namely, those endorsing customary beliefs compared to those not endorsing such beliefs, but was not significant in differentiating these categories from that of being unsure. The challenges to testing behaviour from incorrect AIDS knowledge may be amplified by adherence to customary beliefs that discount scientific explanations about the cause of AIDS. Interventions are required to specifically address misinformation or incorrect knowledge about AIDS derived from traditional beliefs, and should explicitly target persons who either endorse such beliefs or are somewhat equivocal about them. The role of peer educators is highlighted. Traditional healers, given their credibility and status within many traditional cultures, may also have an important role to play in this regard.